An Overview of Marketed Nucleoside and Nucleotide Analogs. Issue 3 (9th March 2022) - De Jonghe, Steven; Herdewijn, Piet
Abstract: Nucleos(t)ide chemistry has been the subject of intense research, mainly because of the promising antiviral and antitumoral activity associated with this compound class. Numerous analogs have been synthesized over the past decades, yielding a number of derivatives that have reached the status of marketed drugs. Herein, an overview of the nucleos(t)ide analogs that have received marketing approval is given. The review is divided into several sections, including antiviral and antitumoral nucleoside analogs as well as nucleoside analogs that have received marketing approval in other therapeutic areas. © 2022 Wiley Periodicals LLC.